Interpretation of Crossmatch reports in a patient with Lupus Nephritis - Shafi q Ahmad Chughtai; Ajay Kumar Sharma; Ahmed Halawa (Archives of Organ Transplantation - Peertechz Publications, 2017)
Acute rejection (AR) is a major issue in renal transplantation which requires hospital admission, invasive investigations, and loss of allograft if it does not resolve with timely treatment. The workup for renal transplantation involves assessing potential recipient's and donor's tissue type. To predict the possibility of having a successful transplant offer, calculated panel reactive antibodies (cPRA) are used. The risk AR is predicted by tests such as cytotoxicity crossmatch, flow cytometry crossmatch, and identification of donor-specific antibodies using solid phase assays. Virtual crossmatch can be employed in selected cases to reduce cold ischemia time. None of these tests are to be taken in isolation. It is important to be aware of limitations of every technique. In addition, patient's serum is tested regularly to determine the presence of antibodies, as antibody titers may fall or new antibodies may surface. Interpretation of the results of these tests can be quite changing. Transplant clinicians need to be aware that autoimmune diseases, blood transfusions, pregnancy or infections can sensitize a recipient and thereby add to a clinical dilemma.